EFFECT OF TIME FERMENTATION OF SOYBEAN TEMPE TO TRIPSIN ACTIVITY - Retno Arianingrum; Eddy Sulistyowati; Das Salirawati (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2007)
The aim of the research is to study the effect of the duration of fermentation process toward the content of soluble protein in tempe from soybean, and the activity of trypsin enzym toward that protein.The content of soluble protein was analyzed by Lowry method using casein as solution standard, and the tripsin activity was determined by Anson method. The duration offermentation process were 0,24,48,72, 96, and 120 hours. The research indicated that the content ofsoluble protein in tempe duringfermentation process for 0, 24, 48, 72,96, and 120 hours were 0.172; 0.212; 0.217; 0.212; 0.197, and0.158% (wlw) respectively, and the activity of trypsine toward the that soluble protein were 1.35; 2.33; 2.73; 2.13; 1.17 and o. 78 unit. It was indicated that the duration of fermentation process influenced thecontent of soluble protein and tripsin activity. The highest of trypsin activity was infermentation process for 48 hours.